RECONSTRUCTION ON DEVELOPING TEACHER CREATIVITY THROUGH TRANSFORMATIONAL LEADERSHIP AT SENIOR HIGH SCHOOL - Mahmud, Hilal (PEOPLE: International Journal of Social Sciences, 2020)
This study aims to find, analyze, and describe information about internal and external factors that contribute to teacher creativity development, alternative strategies that can be determined, and priority strategies that can be applied in teacher creativity development at Senior High School. This research a field research using descriptive-analytic method. Data obtained from observation, literature study, key informants, and experts involved in teacher creativity development at Senior High School. The result of this study indicates three things. First, the internal factors are having an interesting and inspiring vision, but it is inadequate in the availability of infrastructure. External factors are the government's commitment but need to accommodate the increasing demands and expectations of the community towards improving teacher competence. Second, alternative strategies for developing teacher creativity are implementing integration strategies. Third, priority strategies are teacher empowerment-based development blueprints, program synchronization through partnership, enhancing cooperation and partnerships to increase principal managerial competencies and skills, as well as the fulfillment of teachers' facilities and needs.